Effect of process variables on the physicochemical and rheological properties of yogurt - Paz Díaz, Héctor J. (2021)
In this research, the effect of the lactic starter culture, the fermentation time, the incubation temperature and the fat percentage on the firmness and consistency of a fermented milk drink was evaluated through physicochemical characteristics of total acidity, pH, syneresis, and flow behavior. The purpose was to find the best formulation that extends the shelf life of yogurt, leading to an improvement in the manufacturing process of a local dairy company in Barrancabermeja (Santander, Colombia). Quality criteria were evaluated by means of the percentage of acidity and pH of the yogurt, as well as its syneresis and rheological parameters during a storage time of 24 h and 7 d of storage in refrigeration. Acceptable quality parameters were obtained for the yogurt prepared with an inoculum concentration of 2%, an incubation temperature of 40°C and an incubation time of 150 min. In addition, better properties of firmness and consistency were found with absence of syneresis and viscosity in the accepted range, for this dairy product.